PSYCHOLOGICAL CONFLICTS ON THE MAIN CHARACTERS IN NETFLIX ORIGINAL MOVIE “ALL THE BRIGHT PLACES” BY BRETT HALEY - Althaf, Khusnul Muthiah; Nur, Riola Haya (ELITERATE : Journal of English Linguistics and Literature Studies, 2022)
In the movie, psychological conflict, often known as the intrapersonal conflict that is described as a conflict that originates from inside the individual of a character. The researchers analyze the intrinsic aspects of the psychological conflict of the main characters in “All the Bright Places” movie by using the theory of Kurt Lewin (1936). This theory was chosen by the researchers because there has not been a study that analyzes using the theory from Kurt Lewin in “All the Bright Places” movie. This study aims to investigate the types of psychological conflicts faced by the main characters, Theodore Finch and Violet Markey. In addition, the researchers also want to explore and examine the causes and how the two main characters resolve their psychological conflict. The research method that the researchers use is a qualitative descriptive method. This research produced several findings. The psychological conflicts that Finch faced resulted in him developing a mental illness which was influenced by his family environment which was not harmonious, his father had an affair, his mother was often away, and since he was young he was often beaten by his father which not only left scars but also marks on his mind. Meanwhile, Violet is faced with a psychological conflict due to a car accident that happened to her and her sister. From this psychological conflict, the researchers found that the cause of the conflict caused Finch’s personality as an adult to become out of control, his emotions were unstable, and he had difficulty conveying the problems he was facing. In contrast to Violet Markey, she has had a sense of trauma and guilt since her sister died, which causes her personality to change to be quiet and always gloomy. Then proceed with the resolution or settlement of this psychological conflict where the researchers found that there was a positive resolution from Violet’s character who managed to recover from her trauma while a negative resolution occurred in Finch because he ended his psychological conflict by committing suicide.